2015
DOI: 10.1039/c5ra13414e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and pyrolysis characteristics of PNIPAM-grafted SiO2hollow spheres loading vitamin C

Abstract: Thermo-responsive poly(N-isopropyl acrylamide)-grafted SiO 2 hollow spheres (PSHS) were successfully prepared by a multi-step reaction, and then they were used to load vitamin C (VC). Pyrolysis characteristics and kinetic and thermodynamic parameters of PSHS loading VC were measured via thermogravimetric analysis (TGA). Two peaks at 193.03 C and 247.56 C were obtained in the DTG curve of PSHS loading VC, which corresponded to the decomposition of the physically absorbed VC and bound VC molecules formed by hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…The first corresponds to 0.1 < α < 0.3 (390–425) °C and the second to 0.4 < α < 0.6 (433–445) °C (Table 7). It has been reported that this behavior occurs when E a is dependent of conversion, because the degradation process takes place in multi-steps, that is, where the mechanism of thermal decomposition is not known or complex [69,70]. Some works report that the first stage (0.1 < α < 0.3) is associated with the breaking of weak bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first corresponds to 0.1 < α < 0.3 (390–425) °C and the second to 0.4 < α < 0.6 (433–445) °C (Table 7). It has been reported that this behavior occurs when E a is dependent of conversion, because the degradation process takes place in multi-steps, that is, where the mechanism of thermal decomposition is not known or complex [69,70]. Some works report that the first stage (0.1 < α < 0.3) is associated with the breaking of weak bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The thermogravimetry data were tested in the Coats–Redfern (CR) method, because it considers the mechanism of thermal decomposition. This is an integral version of the Arrhenius method that was employed for the determination of kinetic parameters in the thermal decomposition processes (Equation (8)) [70,75]. [ln(g(α)T2)]y=ln(normalARβE)[ERT]x…”
Section: Resultsmentioning
confidence: 99%
“…Figure a represents the TGA curve of bare SiO 2 microspheres. The difference in the weight loss (%) between SiO 2 ‐NH 2 and SiO 2 ‐Br microspheres (Figure b ) at 800 °C is ∼1.2 %, while the weight loss difference observed between the SiO 2 and PNIPAM@SiO 2 corresponding to pyrolysis of PNIPAM is ∼17.4 %, which further validates the formation of PNIPAM on the surfaces of SiO 2 (Figure c ) ,.…”
Section: Resultsmentioning
confidence: 99%
“…All these samples ehixibit weight losses below 100 8C due to the desorption of water molecules. Figure 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 tion of PNIPAM on the surfaces of SiO 2 (Figure 2c) [37,39]. Figure 3 shows SEM images of SiO 2 microspheres, SiO 2 -Br, and PNIPAM@SiO 2 microspheres (polymerization time of 8 h) and Hb/PNIPAM@SiO 2 composite.…”
Section: Characterization Of Pnipam@sio 2 Core-shell Microspheresmentioning
confidence: 99%
“…6 (a) TEM image of solid silica spheres, (b) TEM and (c, d) SEM images of mesoporous hollow silica nanorattles, (e) TEM image of mesoporous hollow silica microspheres [58] 球。其独到之处在于: 利用有序介孔中空有机硅纳 米粒子的"拓扑变换", 通过"原位框架热解法" [61] Fig. 7 SEM images of hollow silica microcapsule [61] 中空 [69][70][71] , 即首先制备出中空SiO 2 微球, 再将其浸入到客体材 料或其分散液中, 通过物理吸附作用来负载客体材 料。但由于中空SiO 2 微球的孔径大小决定了可吸附 到孔内的客体分子的尺寸大小, 因此只有少数小尺 寸的分子可通过壳层上的介孔渗透到中空SiO 2 微球 的内部, 比中空SiO 2 微球孔径大的大尺寸分子则难 以被引入到空腔中 [72] 。所以浸渍法封装效率较低, 客体材料前期释放速度过快, 持续释放效果相对较 差, 而且对客体材料的亲水性要求较高。为了解决 上述缺陷, Wang等 [73] [74][75] 。而为了实现客体分子的控制释放, 则需要 在载体材料上修饰一些刺激响应的 "开关分子" [76][77] , 目前常见的刺激条件包括pH [78] 、温度 [79] 、光 [80] 、 生物分子 [81] 、酶 [82] 和DNA分子 [83] 等。 桂万元等 [84] 图9所示。在此研究基础上, Hu等 [86] 还用上述杂化 中空微球负载维他命C, 也具有良好的温度控制释 放特性。 图 8 不同 pH 下介孔中空 SiO 2 微球的控制释放曲线图 [84] Fig. 8 Controlled release curve under different pH of hollow mesoporous silica microspheres [84] 图 9 杂化中空微球和纯中空微球的香精释放曲线图 [85] Fig.…”
unclassified